Firm Size on IDX BUMN 20 Stock Prices: The Role of Mediating Activity and Profitability - Mochammad Ikhlas Ruri Diens Baihaqi; Wawan Ichwanudin; Enis Khaerunnisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates if firm size increases stock prices using activity and profitability as mediating variables. It employs a quantitative causality method using secondary data from financial reports on firm websites and the IDX. The sample includes companies listed in the IDX BUMN 20 index from 2018-2021, using non-probability sampling and unbalanced panel data estimated with a random effects model. Data analysis involves descriptive statistics, mediation regression, and path analysis with Eviews 12 software. Results indicate firm size and profitability positively impact stock price, firm size positively impacts profitability, activity does not impact stock price, and activity and profitability do not mediate the firm size-stock price relationship